Poland's place in Europe : General Sikorski and the origin of the Oder-Neisse line, 1939-1943 - Terry, Sarah Meiklejohn, 1937- (Princeton University Press, 1983)
The author explores a variety of questions related to General Sikorski's policies, such as his effort to maintain an independent Polish Arms' in the Soviet Union. Drawing on extensive British, American, and Polish archives, her work describes the defeat of a radical solution to the perennial instability of Central Europe. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.